STRATEGI DINAS KOPERASI DAN UMKM KABUPATEN JENEPONTO DALAM PEMASARAN PRODUK MAKANAN BERBAHAN DASAR KUDA - Nurfatiha, Nurfatiha; Mappamiring, Mappamiring; Harakan, Ahmad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study purposed to find out the strategy of the Department of Cooperatives and UMKM in Jeneponto Regency in marketing horse-based food products using qualitative research methods, the number of informants was 7 people. The results of the research were 1) product strategy consisting of collaboration with agencies, conducting seminars and training, participating in regional innovation exhibitions, prioritizing customer satisfaction, durability, selection of raw materials and packaging as well as flavor variants. However, only three horse-based food UMKM were recorded. 2) the price strategy was based on the price of horse meat ingredients. 3) The place strategy, namely UMKM were mostly located on the side of the main street Jeneponto Regency, where it was clean and comfortable, the food was cooked halal and hygienic. 4) promotion strategies such as making a Jeneponto specialty food house, holding exhibitions, giving souvenir food to officials who made regional work visits. Meanwhile, some UMKM had not implemented an effective promotion strategy. The implementation of the program to increase creativity and innovation carried out by the Office of Cooperatives and UMKM in Jeneponto Regency was not felt evenly.